MicroRNAs targeting VEGF are related to vascular dysfunction in preeclampsia. Issue 8 (27th August 2021) - Witvrouwen, Isabel; Mannaerts, Dominique; Ratajczak, Jessica; Boeren, Evi; Faes, Ellen; Van Craenenbroeck, Amaryllis H.; Jacquemyn, Yves; Van Craenenbroeck, Emeline M.
Abstract: In preeclampsia (PE), pre-existent maternal endothelial dysfunction leads to impaired placentation and vascular maladaptation. The vascular endothelial growth factor (VEGF) pathway is essential in the placentation process and VEGF expression is regulated through post-transcriptional modification by microRNAs (miRNAs). We investigated the expression of VEGF-related circulating miR-16, miR-29b, miR-126, miR-155 and miR-200c in PE vs healthy pregnancies (HPs), and their relation with vascular function, oxidative stress (OS) and systemic inflammation. In this case–control study, 24 women with early PE (<34 weeks) were compared with 30 women with HP. Circulating microRNA levels (RT-qPCR), OS and systemic inflammation were assessed in plasma samples (PE 29.5 vs HP 25.8 weeks) and related to extensive in vivo vascular function (flow-mediated dilatation (FMD), modified FMD (mFMD), carotid-femoral pulse wave velocity (CF-PWV), heart rate corrected augmentation index (AIx75) and reactive hyperemia index (RHI)). FMD, CF-PWV, AIx75 and RHI were all significantly impaired in PE ( P <0.05). PE patients had reduced levels of miR-16 (5.53 ± 0.36 vs 5.84 ± 0.61) and increased levels of miR-200c (1.34 ± 0.57 vs 0.97 ± 0.68) ( P <0.05). Independent of age and parity, miR-16 was related to impaired FMD (β 2.771, 95% C.I.: 0.023–5.519, P =0.048) and mFMD (β 3.401, 95% C.I.: 0.201–6.602, P =0.038). Likewise, miR-200c was independently associated with CF-PWV (β 0.513, 95% C.I.: 0.034–0.992, P =0.036). In conclusion, circulating levels of miR-16 were lower in PE, which correlated with impaired endothelial function. Circulating miR-200c was increased in PE and correlated with higher arterial stiffness. These findings suggest a post-transcriptional dysregulation of the VEGF pathway in PE and identify miR-16 and miR-200c as possible diagnostic biomarkers for PE.